Approaches to Strategic Crisis Management of Enterprises in Ukrainian Bessarabia: Socio-Economic Factors - Moskaliuk, Serhii (Journal of Danubian Studies and Research, 2024)
The intense phase of Russian aggression has changed the geo-economic role of different regions of Ukraine. Thus, the southwestern part of Odesa region has become the center of export and import operations of our country. Accordingly, territorial communities and industrial enterprises (organizations) have the opportunity to integrate into new logistics chains to form the basis for their effective development. An important factor in understanding the approaches to strategic crisis management of organizations in Ukrainian Bessarabia is the SWOT analysis of the region's development. This scientific approach identifies internal advantages and disadvantages, as well as opportunities and threats.